Clinical features and therapeutic outcomes of patients with papillary thyroid microcarcinomas and larger tumors. Issue 5 (May 2019) - Zheng, Wei; Wang, Xuan; Rui, Zhongying; Wang, Yi; Meng, Zhaowei; Wang, Renfei
Abstract : Objective: The aim of this study was to identify clinical features and therapeutic outcomes of patients with papillary thyroid cancer (PTC) according to tumor diameter and evaluate the correlation of neck lymph node (LN) involvement of papillary thyroid microcarcinoma (PTMC) according to patients' age. Patients and methods: We divided 467 patients into two groups according to tumor diameter: PTMC group (⩽1 cm) and non-PTMC group (>1 cm). The clinical data were analyzed retrospectively. Thereafter, we divided the PTMC patients into three subgroups according to age: young subgroup (<45 years), middle subgroup (45–54 years), and old subgroup (≥55 years). A further study about clinical features, especially the neck LN involvement in three subgroups, was analyzed. Results: All patients received radioiodine ablation at least once. There were more patients with a single cancer lesion and cancer in the unilateral lobe, less number of neck LN involvement, fewer patients with neck lymph node metastasis (LNM), and more patients with Hashimoto's thyroiditis in PTMC group than in non-PTMC group. At the further evaluation, 58.03% patients maintained clinical remission, which was more in the PTMC group than in non-PTMC group. There was no significant difference in recurrence, but the disease-free survival rate of patients in the PTMC group was higher than in the non-PTMC group. In the PTMC group, the radioactive iodine curative ratio in younger patients is lower than that in the other two subgroups. Both the LNM and central LNM (CLNM) rates were significantly higher in young patients compared with older patients. In addition, the LNM-positive group had more male patients, larger tumor size, and higher thyroglobulin antibody level. Both LNM and the CLNM rates were significantly higher in the young subgroup than in the older subgroup. Young and middle age and extrathyroid extension were independent risk factors for neck LNM. Unlike LNM, young age, extrathyroid extension, and male sex were independent risk factors for CLNM. Conclusion: Some PTMCs were less aggressive and the therapeutic outcomes of them were better than non-PTMC. Moreover, PTMCs in young patients were more aggressive, especially in LNM. Hence, clinicians should consider an individualized treatment according to tumor characteristics and age to achieve better therapeutic efficacy.